Harnessing synergies of crop-livestock integration for climate-smart agriculture - Mulila-Mitti, Joyce; Odubote, Kolawole; Ajayi, Oluyede C. (Technical Centre for Agricultural and Rural Cooperation, 2019)
Integrated crop-livestock systems that provide synergies towards more resilient climate-smart agricultural production systems are possible despite the recognised competition between crops and livestock enterprises. To make this work, it is necessary to understand the trade-offs and capitalise on the opportunities provided through integration.